A novel design method of organic Rankine cycle system harvesting waste heat of heavy‐duty trucks based on off‐design performance. Issue 2 (7th November 2020) - Shi, Xiaolei; Wang, Xuan; Cai, Jinwen; Gao, Yan; Tian, Hua; Shu, Gequn
Abstract: The organic Rankine cycle (ORC) system can effectively recover waste heat from engines of heavy‐duty trucks, and is a promising method to improve the efficiency of on‐board engines. However, engine operating conditions fluctuate greatly while driving, the waste heat recovery system must often work under off‐design conditions, which significantly affects system performance. Further, different component structures can also affect the off‐design performance of the system. Thus, a novel design method of preheating organic Rankine cycle (P‐ORC) system harvesting waste heat of heavy‐duty trucks based on off‐design performance is proposed in this study. The design method includes selection of the optimal types of components and design point to optimize the comprehensive performance of the waste heat recovery system in all road conditions. In this study, different heat exchanger combinations are applied to the P‐ORC system to obtain six different design systems. According to the principle of uniform coverage, the scatter diagram of exhaust temperature and mass flow rate of the engine under real road conditions are discretized into 19 alternative design points. Each system is designed with 19 discretized design points, and a total of 114 design systems are obtained. The optimal heat exchanger combination and design point are selected based on the off‐design performance. It is concluded that a P‐ORC system using a combination of plate preheater, finned tube air cooler, and shell‐tube evaporator is the optimal system. The optimal design point number is 10, and the corresponding engine speed at D P 10 is 1471 rpm, the engine torque is 474 Nm, the occurrence probability is 14.48%, the exhaust temperature is 350°C, the exhaust mass flow rate is 0.11 kg/s, and the maximum combined net power output is 4.26 kW. The results reveal that the optimal design point of the system can be selected at the design point with medium engine load and high occurrence probability. It guides the system design toward a more practical direction, so as to obtain an optimal system that could operate efficiently and recover more waste heat under the full working conditions of the engines. This novel design method can be extended for other cycle configurations. Abstract : This study proposes a comprehensive design method for an ORC waste heat recovery system for ICEs in HDVs optimizing the selection of components and design points based on off‐design performance. It is concluded that a P‐ORC system using a combination of plate preheater, finned tube air cooler, and shell‐tube evaporator is the optimal system. The optimal design point of the system can be selected at the design point with medium engine load and high occurrence probability.